The middle role of the organizational structure in relation to the capabilities of the senior leadership with the effectiveness of the decision - Hamid, Adam Ahmed Mousa (Journal of Economic, Administrative and Legal Sciences, 2017)
The objective of the study was to investigate the effect of the intermediate role of the organizational structure in the relation of the abilities of the senior leadership and the effectiveness of the decision. The analytical descriptive method was used, where a questionnaire was designed to collect data from the study community, and 50 questionnaires were distributed, 41 of which were valid for analysis (82%). There is a positive relationship between senior leadership abilities and decision-making. There is a positive relationship between senior leadership and organizational structure. There is a positive relationship between decision making and organizational structure. The organizational structure mediates the relationship between senior leadership abilities and decision-making. A number of statistical methods were used in the study such as arithmetic mean, standard deviation, alpha kernobakh coefficient, global analysis, Pearson correlation coefficient and regression analysis. The study reached a number of results, including: - (1) the abilities of senior leadership have a positive impact on the effectiveness of the decision. (2) The effectiveness of decisions is influenced by the characteristics of the organizational structure. (3) The organizational structure mediates the relationship between senior leadership capacity and decision effectiveness in organizations. The study recommended the possibility of conducting further research related to measuring the impact of the senior management style on management functions and introducing more variables to construct the model of the proposed studies in addition to applying the study in other sectors of business organizations.